The New Jersey Colony - Italia, Bob (Edina, Minnesota ABDO Publishing Company, 2001)
Provides a history of New Jersey from before the arrival of European explorers in the 16th century to its statehood in 1787.
Keywords: New Jersey - History - Colonial period, ca. 1600-1775.